Banana Heart Sap Experiment - Wirakesuma, I Nengah; Mudana, I Wayan; Kondra, I Wayan; Mustika, I Ketut; Sujana, I Wayan (Journal of Social Science, 2024)
A unique and interesting creative process using banana blossom sap as a medium. Banana flower sap has specific characteristics compared to other synthetic colors. Banana flower sap tends to display typical milky white, gray, light brown, yellowish-green, red and dark brown colors. Painting using banana blossoms starts from picking the banana blossom. Exploration of the technique of cutting the stem of the banana flower until the sap oozes out and drips onto the canvas. Since then I have been practicing spontaneously using banana sap, involving movements of my fingers, pressing the banana flower gently, medium and hard. The effect of the pressure of the banana flower sap produces natural colors, according to the intensity of the movement of the fingers on the canvas. The method used is carried out spontaneously, following the stages of the art creation process (E4): Existence, Exploration, Experimentation and Evaluation. Realization (E4) represents the existence of my creative process. Utilization of fine art elements such as light, point, line, space, plane, color, texture and composition. The resulting works of art include the following titles: Banana Sap Color 1, Banana Sap Color 2, Banana Sap Color 3, and so on. The use of banana blossom sap is driven by the need to express the soul in order to produce new works of art of high quality and have high aesthetic values